Humorous Da'wah and Negotiated Digital Piety: Promoting Inclusive Religious Engagement in Online Public Spheres - Novita Sugiestian; Amin, Sitti Jamilah; Muhammad Qadaruddin; Wahyuddin (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2025)
Within the framework of the growing significance of social media as a platform for religious expression, humorous da'wah arises not merely as a communicative tactic but also as a means of navigating piety, authority, and audience interaction in digital public spheres. This research seeks to examine the influence of humour on audience reactions, the interpretation of religious messages by netizens, and the reflection of broader socio-cultural dynamics in digital interactions among Muslim online communities. This study employs a qualitative digital reception methodology, integrating computational sentiment analysis with thematic and discourse analysis to examine 1,000 user comments gathered via Apify. The data were evaluated with tools from Communalytic.org, such as the Civility Analyser, Sentiment Analyser, Topic Analyser, and Network Analyser, to discern emotional patterns, discourse themes, and interaction structures. This methodological integration facilitates a sophisticated comprehension of how audiences interpret meaning in platform-mediated religious communication. The results indicate that netizen reactions are primarily neutral (61.76%), followed by positive (14.71%) and negative (23.53%) views, suggesting a trend of negotiated reception rather than polarised involvement. Humour serves as a mechanism for low-conflict religious discourse, mitigating animosity and sustaining relatively low levels of toxicity in the commentary environment. The commentary discourse illustrates a process of negotiating digital piety, wherein listeners interpret, modify, and occasionally challenge religious teachings according to their social and cultural settings. This study enhances the scholarship on digital Islam by illustrating how humorous da'wah functions within platform logics to generate inclusive and emotive forms of religious communication. It emphasises the significance of comedy in promoting civil online discourse and provides insights into the reconfiguration of religious authority within participatory media contexts.